Emergence of an outbreak-associated Clostridium difficile variant with increased virulence - Guzman-Verri, Caterina (2015)
The prevalence of Clostridium difficile infections has increased due to the emergence of epidemic variants from diverse genetic lineages. Here we describe the emergence of a novel variant during an outbreak in a Costa Rican hospital that was associated with severe clinical presentations. This C. difficile variant elicited higher white blood cell counts and caused disease in younger patients than did other strains isolated during the outbreak. Furthermore, it had a recurrence rate, a 30-day attributable disease rate, and disease severity as great as those of the epidemic strain NAP1. Pulsed-field gel electrophoresis genotyping indicated that the outbreak strains belong to a previously undescribed variant, designated NAPCR1. Whole-genome sequencing and ribotyping indicated that the NAPCR1 variant belongs to C. difficile ribotype 012 and sequence type 54, as does the reference strain 630. NAPCR1 strains are resistant to fluoroquinolones due to a mutation in gyrA, and they possess an 18-bp deletion in tcdC that is characteristic of the epidemic, evolutionarily distinct, C. difficile NAP1 variant. NAPCR1 genomes contain 10% more predicted genes than strain 630, most of which are of hypothetical function and are present on phages and other mobile genetic elements. The increased virulence of NAPCR1 was confirmed by mortality rates in the hamster model and strong inflammatory responses induced by bacteria-free supernatants in the murine ligated loop model. However, NAPCR1 strains do not synthesize toxin A and toxin B at levels comparable to those in NAP1 strains. Our results suggest that the pathogenic potential of this emerging C. difficile variant is due to the acquisition of hypothetical functions associated with laterally acquired DNA.